PENERAPAN MEDIA KARTU KATA BERGAMBAR UNTUK MENINGKATKAN SKILL MEMBACA ANAK USIA DINI DI RA ALWASLIYAH BANGUN 17 KECAMATAN GUNUNG MALELA KABUPATEN SIMALUNGUN - Yusniarti Yusniarti; Rizka Adha Miranti; Muhammad Wahyudi (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2022)
The purpose of this study was to analyze the application of picture word card media to improve early childhood reading skills in Ra Alwasliyah Bangun 17, Gunung Malela District, Simalungun Regency. Learning media is an important aspect that supports the learning process for early childhood in order to develop all aspects of development for educational preparation at the next level. Very many learning media have been applied and developed in early childhood education, therefore this study aims to describe early childhood learning media. This type of research is qualitative research. The process of data collection in this type of research is: observation and interview. The results of this study explain that so many learning media can be applied by educators according to certain aspects such as aspects of vocabulary development, cognitive, speaking, creativity, numeracy, language, social emotional, physical motor and reading. One of the learning media that plays an active role in developing early childhood reading skills is picture word card media. Thus, the application of picture word card media in Ra Alwasliyah Bangun 17 can be done well.